Engineering constructed of high selectivity dexamethasone aptamer based on truncation and mutation technology - Qin, Yadi; Qin, Yanan; Bubiajiaer, Hayilati; Chen, Fengxia; Yao, Jun; Zhang, Minwei (Frontiers in Bioengineering and Biotechnology, 2022)
Various biosensors based on aptamers are currently the most popular rapid detection approaches, but the performance of these sensors is closely related to the affinity of aptamers. In this work, a strategy for constructed high-affinity aptamer was proposed. By truncating the bases flanking the 59nt dexamethasone (DEX) original aptamer sequence and then introducing base mutations, the 33nt aptamer Apt-M13 was obtained. The dissociation constant (Kd) was determined to be 200 nM by Graphene oxide (GO)-based fluorometry. Finally, Apt-M13 was used for a label-free colorimetric aptamer sensor based on gold nanoparticles, the LOD was 3.2-fold lower than the original aptamer described in previous works. The anti-interference ability of DEX analogs is also further improved. Therefore, the proposed aptamer optimization method is also expected to become a general strategy for various aptamer sequences.